VIRTUAL TOUR OF SADENG BEACH TOURISM ROUTE USING THE MULTIMEDIA DEVELOPMENT LIFE CYCLE METHOD - Nurcahyani Dewi Retnowati; Dwi Nugraheny (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2020)
Gunung Kidul is a tourism potential area, one of which is a beautiful beach. Among the beautiful beaches and tourism potential is Sadeng beach. One way to publicize tourism is presented in the form of Virtual tour, so in this study the theme is about the Virtual tour of Sadeng Beach. Virtual tour of Sadeng Beach is one of the media that can be used to help prospective tourists explain about tourist routes from Bukit Bintang to Sadeng Beach, public facilities that are traversed, and detailed information about attractions. The virtual tour of Sadeng Beach tour route uses the Multimedia Development Life Cycle (MDLC) method which consists of determining the concept, design, determining material or data, making, testing, and evaluating. Virtual tour application test results show that this application can be run with a minimum Core i3 specifications with 4GB RAM and Windows 7 (64 bit) operating system with 5 screen resolution options and 6 graphics quality options. User test results with 30 respondents and calculations using a Likert scale showed 75.83% of this application included in the category of very good in terms of mentioning the time and distance from the beginning to the end of the tour.